Study the correlation between alleles of MCT1 gene and enduring performance in handball players - Al-Lami, H. A. A.; Khaleel, S. H.; Yonis, S. D. (Journal of Human Sport & Exercise, 2020)
The current study aimed to determine MCT1 gene A1470T polymorphism is associated it with enduring performance among elite handball players young. The community of study was chosen 100 young players of Iraqi clubs in handball game which their length (171.83 ± 3.060 cm), weight (68.33 ± 2.160 kg) and age (24.4 ± 3.782 years). Genotyping of A1470T polymorphism of the MCT1 gene was done by the PCR-RFLP technique lactate measurement of 100 handball players was examined after testing the endurance of defensive and attack performance. Frequencies of genotypes in 100 players were AA genotype (60%), AT genotype (30%) and TT genotype (10%).The mean of endurance capacity was significantly higher in AA genotype (1.01 ± 0.04 min) versus AT genotype (1.10 ± 0.01 min). (AA + AT) genotypes versus TT genotype (1.14 ± 0.01 min). Mean of blood lactate concentration was significantly higher in AA genotype (16.23 ± 0.35 mMol) versus (AT + TT) genotypes (13.48 ± 0.18; 11.66 ± 0.13 mMol) respectively. We concluded that the MCT1 gene A1470T polymorphism enhances enduring performance in elite handball players.